1786 Mass. Acts 346 - (:unkn) unknown (My University, 1786)
§§ 1-2, An Act to Prevent Routs, Riots, and Tumultuous assemblies, and the Evil Consequences Thereof. § 1: Be it therefore enacted by the Senate and House of Representatives, in General Court assembled, and by the authority of the same,§That from and after the publication of this Act, if any persons to the number of twelve, or more, being armed with clubs or other weapons; or if any number of persons, consisting of thirty or more, shall be unlawfully, routously, riotously or tumultuously assembled, any Justice of the Peace, Sheriff or Deputy-Sheriff of the county, or Constable of the town, shall, among the rioters, or as near to them as he can safely come, command silence while proclamation is making, and shall openly make proclamation in these or the like words:
Keywords: GOING ARMED